1974
DOI: 10.1002/food.19740180617
|View full text |Cite
|
Sign up to set email alerts
|

Über Samenproteine. 4. Mitt. Isolierung der Globulin‐Hauptkomponente aus Sonnenblumensamen

Abstract: Es wird die Isolierung des sedimentationsanalytisch und gelchromatographisch einheitlichen 11‐S‐Globulins aus Sonnenblumensamen aus 10% Natriumchlorid enthaltenden Extrakten mit Hilfe einer Fällung mit Wasser und nachfolgender wiederholter Chromatographie des albuminfreien Rohglobulins an Sephadex G‐200 beschrieben. Mit der gleichen Verfahrensweise gelingt die Isolierung einer in geringen Mengen anwesenden 7‐S‐Komponente. Die Sedimentationskonstante s20,w des 11‐S‐Globulins beträgt 11,8 S. In Lösungen niedrige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

1975
1975
2007
2007

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…According to the dissociation of the helianthinin depending on the ionic strength we predicted the appearance of at least two components during the ionexchange chromatography using a salt gradient [2]. As the present results show, the 7 S component as the product of dissociation appears, indeed, during the elution of the protein from the DEAESephadex column at an ionic strength -0.4 in fraction A.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…According to the dissociation of the helianthinin depending on the ionic strength we predicted the appearance of at least two components during the ionexchange chromatography using a salt gradient [2]. As the present results show, the 7 S component as the product of dissociation appears, indeed, during the elution of the protein from the DEAESephadex column at an ionic strength -0.4 in fraction A.…”
Section: Discussionmentioning
confidence: 64%
“…In order to get a homogeneous 11 S giobulin by purification of the raw globulin on the ion-exchange column without any preliminary purification by gel chromatography, the cryoprecipitated protein [2] was brought directly onto the DEAE-Sephadex column. Molecular weight and some hydrodynamic properties Fig.…”
Section: Ion-exchange Chromatographymentioning
confidence: 99%
“…Nevertheless, various amounts of proteins with 7S sedimentation coefficient have been detected in sunflower seeds 48, 50, 54. These 7S constituents are most likely dissociation products of the 11S globulins, a dissociation which also occurs in soybean glycinin 8, 108–111. Furthermore, sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS‐PAGE) did not show differences between the molecular subunits of the 11S and 7S forms of sunflower globulins under both reducing and non‐reducing conditions 111…”
Section: Sunflower Proteins: Biochemical and Biophysical Aspectsmentioning
confidence: 99%
“…According to Molina et al ,127 helianthinin shows a hexameric form at pH 6–9 (ionic strength ( I ) = 500 mmol L −1 ). It has been reported that in solutions of low ionic strength ( I < 300 mmol L −1 ) the 11S form of helianthinin dissociates into the 7S form (pH 7–8) 108, 129. However, González‐Pérez et al 111 demonstrated that both forms of helianthinin (11S and 7S) are present at near neutral pH over a broad ionic strength range (30–1250 mmol L −1 ), although a higher ionic strength contributes to stabilisation of the 11S form.…”
Section: Helianthininmentioning
confidence: 99%
“…In the case of the 11s globulin from sunflower seed we were able to show that in solutions of low ionic strength a dissociation of the 11s protein with a molecular weight of 305,000 takes place to form 7 s half molecules with a molecular weight of 150,000 (Schwenke et al, 1974;Behlke & Schwenke, 1976). The experimental conditions of determination of the molecular weight of the rapeseed globulin were not published by Gill & Tung (1976) but the poor solubility of their protein prep aration points to a strong aggregation during the freeze-drying process.…”
Section: Stokes Radiusmentioning
confidence: 94%